2001
DOI: 10.1046/j.1440-1827.2001.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors and KIT‐positive mesenchymal cells in the omentum

Abstract: Gastrointestinal stromal tumor (GIST) is currently considered to be derived from the interstitial cells of Cajal (ICC). To test the hypothesis that omental mesenchymal tumor is also a type of GIST, we evaluated the expression of specific molecules in GIST, and c-kit gene mutation in omental mesenchymal tumors, and we identified a possible counterpart of ICC in the omentum. Immunohistochemically, all of the omental mesenchymal tumors (n = 5) were positive for both KIT and CD34, and three of the five tumors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 32 publications
4
88
0
6
Order By: Relevance
“…In our previous studies regarding mutation in c-kit gene exon 11 by PCR-SSCP analysis, lack of a normal allele was seen in some GISTs in the tubular GI tract and the omentum. 11,16) Two cases of GISTs with exon 13 mutation reported by Lux et al also lacked wild-type KIT sequences. 13) Loss of 4q11-12, where the c-kit gene is located, has not been reported using comparative genomic hybridization, 17) microsatellite markers 18) and fluorescence in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies regarding mutation in c-kit gene exon 11 by PCR-SSCP analysis, lack of a normal allele was seen in some GISTs in the tubular GI tract and the omentum. 11,16) Two cases of GISTs with exon 13 mutation reported by Lux et al also lacked wild-type KIT sequences. 13) Loss of 4q11-12, where the c-kit gene is located, has not been reported using comparative genomic hybridization, 17) microsatellite markers 18) and fluorescence in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…They found all five tumors to be positive for CD117 and CD34 staining, while all were negative for smooth-muscle cell markers. More importantly, the authors reported finding KIT immunoreactive CD117 and CD34 cells within specimens of omentum (Sakurai S et al;2001). These findings and those of Yamamoto et al underscore the fact that histologically, EGISTs have a similar appearance to GISTs, and that EGIST is a distinctive entity, different from leiomyosarcomas 1999).…”
Section: Treatment Of the Non-metastatic Disease Approach To The Primmentioning
confidence: 84%
“…It is not well known if extra-gastrointestinal stromal tumors (EGIST) originate from pacemaker cells outside of the GI tract or if mesenchymal cells have the ability to recapitulate the phenotype. Sakurai et al (Sakurai S et al;2001), published their results on the cytological, immunohistochemical, and genetic analysis of 5 omental mesenchymal tumors in 2001. They found all five tumors to be positive for CD117 and CD34 staining, while all were negative for smooth-muscle cell markers.…”
Section: Treatment Of the Non-metastatic Disease Approach To The Primmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,16,18 However, the cellular origin of these so-called extragastrointestinal stromal tumors (EGISTs) is not known, and the occurrence of EGISTs is still discussed controversially. 1 One study could find KIT-positive mesenchymal cells in the normal human omentum; 24 in another study, most cases of EGISTs were re-diagnosed as metastases of normal GISTs or as GISTs that have arisen from the outer muscle coat of the gastrointestinal tract and lost their contact due to an extensive extramural growth pattern.…”
mentioning
confidence: 99%